PERJAMUAN KUDUS BAGI ANAK DALAM GEREJA METHODIST - Samosir, Nettina; Parhusip, Mangatas (Universitas Methodist Indonesia, 2023)
This study aims to find out about the attitude of the Methodist Church in involving children to receive the elements of the communion. The Holy Communion is one of the two sacraments recognized by Protestant Christian churches. This Holy Communion is a direct command from the Lord Jesus to be carried out by His churches on this earth. This can be seen from the words of Jesus who stated